Hitting the brakes in soccer: Individualised thresholds for assessing high-intensity decelerations during matches - Moore, L.; Drury, B.; Hearn, A. (International Journal of Strength and Conditioning, 2026)
There is currently a lack of understanding surrounding how to quantify high-intensity deceleration actions in soccer. Therefore, this study sought to compare the use of arbitrary (ARB) and individualised (IND) high-intensity deceleration thresholds when examining the most demanding passages of play (MDP) and full matches. Fourteen male soccer players (age = 19.44 ± 1.13 yrs.; mass = 79.14 ± 7.88 kg; height = 184.16 ± 5.00 cm) were monitored during competitive matches using global positioning systems (WIMU Pro, RealTrack System SL, Almeria, Spain). IND thresholds were determined as 75% of a subject's peak deceleration ability from match data. ARB values were set as > 4m/s2 with the differences between these high-intensity deceleration thresholds analysed. ARB thresholds resulted in significantly (p < 0.01) larger distance and count metrics compared to IND during both MDP and full matches. These findings highlight the notable differences between ARB and IND high-intensity deceleration thresholds in matches. Thus, it is recommended a modified IND threshold approach is used when analysing the high-intensity deceleration demands of matches and MDP. Practitioners may be inclined to monitor high-intensity decelerations using IND thresholds, as is suggested when measuring other locomotor tasks during soccer training and matches.